New Insights Into the Evolution of C4 Photosynthesis Offered by the Tarenaya Cluster of Cleomaceae - Parma, Daniele F.; Vaz, Marcelo G. M. V.; Falquetto, Priscilla; Silva, Jéssica C.; Clarindo, Wellington R.; Westhoff, Philipp; van Velzen, Robin; Schlüter, Urte; Araújo, Wagner L.; Schranz, M. Eric; Weber, Andreas P. M.; Nunes-Nesi, Adriano (Frontiers in Plant Science, 2022)
Cleomaceae is closely related to Brassicaceae and includes C3, C3-C4, and C4 species. Thus, this family represents an interesting system for studying the evolution of the carbon-concentrating mechanism. However, inadequate genetic information on Cleomaceae limits their research applications. Here, we characterized 22 Cleomaceae accessions [3 genera (Cleoserrata, Gynandropsis, and Tarenaya) and 11 species] in terms of genome size; molecular phylogeny; and anatomical, biochemical, and photosynthetic traits. We clustered the species into seven groups based on genome size. Interestingly, despite clear differences in genome size (2C, ranging from 0.55 to 1.3 pg) in Tarenaya spp., this variation was not consistent with phylogenetic grouping based on the internal transcribed spacer (ITS) marker, suggesting the occurrence of multiple polyploidy events within this genus. Moreover, only G. gynandra, which possesses a large nuclear genome, exhibited the C4 metabolism. Among the C3-like species, we observed intra- and interspecific variation in nuclear genome size as well as in biochemical, physiological, and anatomical traits. Furthermore, the C3-like species had increased venation density and bundle sheath cell size, compared to C4 species, which likely predisposed the former lineages to C4 photosynthesis. Our findings demonstrate the potential of Tarenaya in offering novel insights into the evolution of C4 photosynthesis.